Coordination environment of Ru clusters with in-situ generated metastable symmetry-breaking centers for seawater electrolysis. (November 2022) - Gu, Xiangyao; Yu, Min; Chen, Siqi; Mu, Xueqin; Xu, Zihan; Shao, Wenqian; Zhu, Jinjing; Chen, Changyun; Liu, Suli; Mu, Shichun
Abstract: Seawater electrolysis offers hope for renewable production of green hydrogen. However, its hydrogen evolution reaction (HER) is quite difficulty due to electrode corrosion and undesirable side reactions. More importantly, it is still a big challenge to regulate charge distribution of Ru clusters at atomic level for maximizing the activity. Herein, theory calculations unveil that, substituting partial Ru atoms with atomically dispersedly nonstoichiometric Cdy Sex drives in-situ generation of metastable symmetry-breaking Ru cluster surfaces (Ru/Cdy Sex ) and more atom vacancies, which regulates the coordination environment of Ru atoms and results in optimized Ru−H bond and more channels for H migration. As expected, Ru/Cd0.02 Se4 requires overpotentials as low as 4.2 and 6.3 mV at 10 mA cm −2, and has 8.1 and 9.6 times higher turnover frequency (TOF) than Ru/Sex in alkali and alkaline seawater, respectively, superior to Pt/C and most other catalysts reported so far. Also, it shows very impressive stability over 50 h. This discovery elaborates the activity origin via symmetry breaking and provides deep cognition for hydrogen product from seawater electrolysis. Graphical Abstract: The Cd/Se single-atomic-site doping in Ru clusters (Ru/Cdy Sex ) eﬀectively breaks the Ru symmetry structure, and optimizes Ru coordination environment with atomically dispersed Cd and Se and deficiency, and the Ru−H binding energy, leading to excellent HER catalytic activity in both alkali and alkaline seawater. ga1 Highlights: Tailoring coordination environment of Ru atoms can optimize hydrogen adsorption. Atomic Cd and Se vacancy modiﬁed Ru cluster catalyst is designed and constructed. Charge redistribution at Ru/Cdy Sex interface is due to symmetry structure break. Ru/Cd0.02 Se4 exhibits excellent HER performance in alkali and alkaline seawater. Ru/Cd0.02 Se4 shows very impressive stability over 50 h, superior to Pt catalysts.